Enhancing Employee OCB through Organizational Culture, Organizational Commitment and Work Dicipline - Nurjanah, Annisa Rista; Yulistiana, Reza Dimas; Maryam, Siti; Sunimah, Sunimah (PT FORMOSA CENDEKIA GLOBAL, 2025)
Human resources must be properly given attention to as they are highly valuable assets that continuously contribute to the organization positively. This study purpose to find out about how organizational culture, organizational commitment, and work discipline affect OCB. The method implemented was interview and questionnaire distribution to employees of PDAM Tirta Bhakti Raharja of Majalengka Regency, with 131 respondents in total. The implemented technique for sampling was census method because all populations are included as sample. This study results in the finding that organizational culture positively and significantly affects OCB, organizational commitment positively and significantly affects OCB, work discipline positively and significantly affects OCB, and simultaneously, organizational culture, organizational commitment, along with work discipline positively and significantly affect OCB.